Existence and Uniqueness of Weak Solutions to Variable-Order Fractional Laplacian Equations with Variable Exponents - Yating Guo; Guoju Ye (Journal of Function Spaces)
In this paper, the variable-order fractional Laplacian equations with variable exponents and the Kirchhoff-type problem driven by p·-fractional Laplace with variable exponents were studied. By using variational method, the authors obtain the existence and uniqueness results.